O patrimônio documental arquivístico de São Francisco de Assis com ênfase na plataforma de acesso, descrição e difusão - Mazuco, Fabiana Ciocheta (2018)
The present academic work present san approach on the archival documentary heritage of the institution and it sinvolvement with archival principles and concepts, the implementation of a Municipal File System, the classification and temporality of archival documents, a theoretical approach to chain of custody, as well as the implementation of a platform for access, description and diffusion to digital archival documents, in the Municipal Public Heritage Sector of Sao Francisco de Assis. These documents diplomatically analyzed, are recognizedas archival documentary heritage and represented through a fixed for mands table content. The property registration certificates are examples of source of pro of concerning the municipal public heritage. This study is warranted because understands that the implementationofan access environmentoffers active transparency and warranty of continuable access. There fore, an applied research with qualitative and exploratory approach has been conducted, classifiedas bibliographic and case study. The data collect was obtained by annotation, observations, interviews and documental analysis. There sults of there search corroborate to point to the access flux, temporality of permanent guard and to identify the classification structure. The evolutions of the experiences and the applicability of the methodologies and institutional normative actshaveal so been disrupted. The professional profile of the archivist before the institutional scenary has also been studied. From this perspective, it is understood that the objectives of the research are identified as guiding elements to the work, complementing the implementation of the access platform as a product of this dissertation of Professional Masters in Cultural Heritage and understanding that the preparation of the Classification Plan of Archival Documents and Law Nº. 1007/2016, which establishes the Municipal Public Archive, are also products of the same. As a conclusion, the general objective of the research can besaid that it has been attained, having the AtoM demonstrated to be capableofoffering plainly the continuable access to the digital archival documents in the Municipal Public Heritage Sector, providing the authenticity of the digital documents according to the international patterns.